Network Security Strengthening Strategy Using Mikrotik Firewall on Small to Medium-Scale IT Infrastructure - Ardy Januantoro; Supangat (International Conference of Innovation and Community Engagement, 2024)
The growing concern over cyber attacks, particularly on small to medium-scale information technology infrastructures, has made network security a critical priority. This study focuses on mitigating threats such as unauthorized access and Denial of Service (DoS) attacks through the implementation of a Mikrotik-based firewall. The research methodology includes an analysis of network security needs, comprehensive firewall configuration, and the application of layered security strategies. The implementation utilizes Mikrotik features, including firewall rules, Network Address Translation (NAT), and Layer 7 filters, to enhance resilience against various types of attacks without compromising network performance. The results of this study show that this approach significantly reduces security incidents following the recommended configuration. This research provides practical guidance for network administrators to optimize the use of Mikrotik as an effective firewall solution in protecting small to medium-scale IT infrastructures.